OUTCOME-BASED ENGLISH PHONETICS AND PHONOLOGY COURSE: WHAT DO STUDENTS SAY? - Tasya Amalia; Alies Poetri Lintangsari (UIN Alauddin Makassar, 2021)
This study attempts to report the evaluation of Outcome-based Education (OBE) syllabus application in English Phonetics and Phonology course based on students’ perspectives. The data were collected through a questionnaire with a sample of 112 participants. The participants are the students enrolling English Phonetics and Phonology Course in the English Language Education Study Program, Faculty of Cultural Studies, Brawijaya University. Outcome-based Education Course Evaluation questionnaires were distributed at the end of the course. The obtained result showed students’ positive response towards the implementation of the Outcome-based Education framework in the English Phonetics and Phonology course. The course evaluation questionnaire revealed students’ acknowledgement of the course preparation by applying the OBE approach. The findings show 44% of 112 participants agree on the five statements asked on the course evaluation questionnaire. However, an issue on students’ confidence in achieving the course outcome has risen with the findings indicating 20% of students who disagree, alluding it as the most disagreed item out of all the items in the questionnaire. Meanwhile, the questionnaire on students’ self-evaluation showed encouraging responses regarding course assessments and activities with the three questions showing the highest score by an average of 23% of students choosing ‘strongly agree’. This study should shed light on the impact of Outcome-based Learning for future educators and researchers.